THE INFLUENCE OF PROFITABILITY, CAPITAL STRUCTURE, SALES GROWTH ON FIRM VALUE WITH FIRM SIZE AS A MODERATING VARIABLE - A'inun Naim, Khumairoh Hafiz; Takarini, Nurjanti (Jurnal Bisnis Manajemen dan Akuntansi, 2026)
Using firm size as a moderating variable, this research examines how profitability, capital structure, and sales growth affect firm value in transportation and logistics companies listed on the Indonesia Stock Exchange between 2021 and 2024. Purposive sampling was used to pick the 27 companies that made up the research sample. The data was analyzed using Moderated Regression Analysis (MRA) to investigate the direct association and moderating effects. The findings demonstrate that profitability significantly raises firm value. On the other hand, sales growth and capital structure have little effect on the value of a company. Additionally, the correlation between firm value and profitability is weakened with firm size. However, the impact of capital structure and sales growth on a business is unaffected by firm size